If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15m + 3m = -18 Combine like terms: 15m + 3m = 18m 18m = -18 Solving 18m = -18 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '18'. m = -1 Simplifying m = -1
| 12y=3(4y-7) | | 10b-9b=2 | | 4-2(3X-2)=2(X-3) | | 8v+12=4(2v+3) | | 2+x*3+2x=21 | | 8x^2+-14x+3=0 | | 1.3p+1=1.6 | | 3x-2x+1=5 | | 62=x-6x+2 | | 7=1x(3+2x) | | -8+4x+4x=-88 | | 2(4x-3)-7(x+1)= | | 10+12x=3(5+3x)-3 | | 175=175-2.75n | | 7y+8=32 | | (0.3x-55)=180 | | (x-10)-0.15(x-10)=50 | | 7x+2y+14=0 | | -8+4x+4x=-8 | | J=7+-3t | | 2x^2+-250x+5000=0 | | -9=2v+9-5v+6 | | 1440=(x-2)*180 | | J=7t+-3t | | 4(x-7)-10=2 | | 2cos(x)+1=0.5 | | 5x^2+28x+-12=0 | | 6+6x=-60 | | 1.25g=15g+.50 | | y=2(1)+2.50(1) | | -4+7x=-46 | | 4+8=8+x |